The lack of target specificity of small molecule anticancer kinase inhibitors is correlated with their ability to damage myocytes in vitro - Hasinoff, Brian B.; Patel, Daywin (Toxicology and applied pharmacology, 2010)
Many new targeted small molecule anticancer kinase inhibitors are actively being developed. However, the clinical use of some kinase inhibitors has been shown to result in cardiotoxicity. In most cases the mechanisms by which they exert their cardiotoxicity are not well understood. We have used large scale profiling data on 8 FDA-approved tyrosine kinase inhibitors and 10 other kinase inhibitors to a panel of 317 kinases in order to correlate binding constants and kinase inhibitor binding selectivity scores with kinase inhibitor-induced damage to neonatal rat cardiac myocytes. The 18 kinase inhibitors that were the subject of this study were: canertinib, dasatinib, dovitinib, erlotinib, flavopiridol, gefitinib, imatinib, lapatinib, midostaurin, motesanib, pazopanib, sorafenib, staurosporine, sunitinib, tandutinib, tozasertib, vandetanib and vatalanib. The combined tyrosine kinase and serine-threonine kinase selectivity scores were highly correlated with the myocyte-damaging effects of the kinase inhibitors. This result suggests that myocyte damage was due to a lack of target selectivity to binding of both tyrosine kinases and serine-threonine kinases, and was not due to binding to either group specifically. Finally, the strength of kinase inhibitor binding for 290 kinases was examined for correlations with myocyte damage. Kinase inhibitor binding was significantly correlated with myocyte damage for 12 kinases. Thus, myocyte damage may be multifactorial in nature with the inhibition of a number of kinases involved in producing kinase inhibitor-induced myocyte damage.